Comparative Evaluation of the Novel bioNexia Legionella Test with the BinaxNOW Legionella Card Assay and the Sofia Legionella FIA Assay for Detection of Legionella pneumophila (Serogroup 1) Antigen in Urine Samples - Congestrì, Francesco (J Clin Microbiol, 2016)
A new immunochromatographic test (bioNexia Legionella; bioMérieux) for the detection of Legionella pneumophila urinary antigen was evaluated in 255 urine samples. The results were compared with those obtained by the BinaxNOW and Sofia Legionella tests. The novel test compared well with those currently in use.